Aquaculture Genome Technologies - Liu (John) , Zhanjiang (Blackwell Pub, 2007)
Overall, Aquaculture Genome Technologies gives a good and comprehensive overview of the principes of genomic tools covering both classical and modern methods, combining clarity and depth besides some space limitations in certain chapters. The book will be of value to postgraduate students, researchers and academics within the field of aquaculture and agriculture, molecular biology and animal breeding... I am convinced that Aquaculture genome technologies will be an important reference for quite some time and I welcome its arrival